Geological Characteristics and Occurrence of Pianyanzi Au Deposit in Daduhe Basin, Sichuan - Yan Zhang; Yin Li; Xin Yin; Cuihua Chen; Jiaxin Wang; Yulong Yang; Fa Zou (Kuangchan zonghe liyong, 2022)
Pianyanzi gold deposit is located in the Daduhe metallogenic belt at the northern end of the Kangyan-Yunnan axis. It is a rare flummagnesite type gold deposit in the world. Produced in the upper sinian dengying formation, the mineral composition is relatively rich, up to 50 kinds of minerals have been identified. The ore type is mainly flummagnesite-quartz type, and the ore body is controlled by both strata and structure. By means of EPMA and SEM, it is found that the gold minerals are mainly fluobesite, pyrite, tetrahedrite and so on. According to the chemical state of gold, the occurrence state of gold can be divided into three categories: independent minerals, complex complexes and lattice gold. According to the distribution relationship between gold and carrier minerals, it can be divided into three categories: encapsulated gold, fissure gold and intergranular gold. The granularity of gold has a large span, mainly concentrated in 2 ~ 10 μm, and belongs to the crystallized gold and microscopic gold.